The use of macro and micro fertilizers in barley crops in field crop rotation on leached chernozem - L. N. Prokina; S. V. Pugaev (Аграрная наука Евро-Северо-Востока, 2023)
The article summarizes the 2020-2021 research results, obtained in a field stationary experiment on leached chernozem in the Republic of Mordovia. The object of the study was spring barley of the Zazersky 85 variety. In its sowings the effectiveness of separate and joint use of the Forsazh (micro) preparation with various doses of mineral fertilizers was studied, including against the background of liming of the soil by 0.5 and 1.0 h.a. in 1999-2000. On average, for two years in the variant without the use of chemicals, the crop yield was 1.82 t / ha. The effect of fertilizers (P40K40, N40-60-80P40K40) was estimated by an increase in the yield of 0.10, 0.40-1.02 t/ha (LSD05 = 0.03 t/ha). The payback of 1 kg a.i. of mineral fertilizers with additional income increased with the rise in the doses of fertilizers applied - 0.94, 1.08, 1.19, 1.38 rubles/rub, respectively. The use of mineral fertilizers significantly increased the mass of 1000 grains and the natural weight of barley grain by 0.6-2.3 g and 9-33 g/l, respectively, and the Forsazh preparation by 0.2 g and 3 g/l. The recommended dose of mineral fertilizers for barley N80P40K40 provides the yield of 2.84 t/ha. Additional use of the Forsazh (micro) preparation will improve the technological indicators of grain quality.